The air allowed for Hair: cultural Inclusivity in Cape Town Private Schools - Richter, Nicolaas (Graduate School of Business (GSB), 2026)
This study explored how parents with children in a sample of Cape Town private schools experience values that shape cultural inclusivity around hair rules, particularly concerning Afrocentric hairstyles. In post-apartheid South Africa, significant efforts have been made to reform the education system, yet hair policies in schools remain a contentious issue, reflecting broader challenges in creating truly inclusive educational environments. However, challenges remain, and inequalities are particularly evident in some private schools where traditional practices may conflict with cultural expression. Using the metaphor of ‘air allowed for hair,' this research examined the space granted for Afrocentric cultural expression within different private school environments. Through a constructivist paradigm and qualitative approach, semi-structured interviews were conducted with 13 parents from diverse backgrounds whose children attend nine private schools and one elite Model C school in Cape Town. AI-generated photos were used as interview tools to facilitate discussions about diverse hairstyles. The study also analysed publicly available data from school websites collected using Python-based web scraping tool. Interpretative phenomenological analysis was employed to examine how school values influence hair experiences. Three distinct categories of schools emerged: faith-based, academic-focused, and Steiner schools, each allowing different degrees of “air” for Afrocentric hair expression. The findings revealed a clear spectrum of inclusivity: faith-based and traditional academic schools typically offered the least "air," maintaining restrictive environments that limited self-expression, while Steiner schools consistently provided the most "air," creating settings that actively welcomed diverse hairstyles. This variation in ‘air allowed for hair' directly reflected each school's underlying value system, with conformity and tradition values correlating with restrictive policies, and self-direction and universalism values enabling greater cultural expression. Parents' experiences highlighted tensions between maintaining traditional school cultures and fostering inclusive environments, while also revealing the complex trade-offs parents navigate during school selection. This research contributes to understanding how private schools in post-apartheid South Africa navigate cultural inclusivity through the lens of hair policies. It demonstrates that while some progress has been made, many institutions still struggle to fully accommodate and celebrate diverse cultural expressions, including Afrocentric hairstyles. These findings have implications for school policy development, parent-school relationships, and broader efforts to decolonise education in South Africa.